Growth and mortality of the mother-of-pearl Pinctada mazatlanica in natural populations of the east coast of Baja California Sur, Mexico - Wright López, Humberto (2009)
The Mexican Pacific mother-of-pearl Pinctada mazatlanica was placed in forbidden fisheries status for the Mexican Federal Government and considered in extinction danger since 1939. This decree was modified in 1994 to allow the capture of spat for research or marine culture. We estimated the growth and mortality of mother-of-pearl from the eastern littoral of South Baja California wild stock in the periods 1992-93 and 1997-99. We used 38 sample stations at 2 bays and 6 insular complexes. The maximum length was 187.22 mm (179.83-195.81 mm, P > 0.95). Seasonal von Bertalanffy growth (ELEFAN I routine) values are: L∞ = 193.31 mm, k = 0.54 year-1, t0 = -0.1805 year, C = 0.49 and WP = 0.75. The growth performance index was Φ’ = 4.305. The total mortality was calculated from a length-converted catch curve Z = 2.03 año -1. Length-weight relationship W(i) = 0.0005418 * L(i)2.7301. The growth parameters were similar to those for Pinctada margaritifera var. cumingi (open ocean wild stocks). The wild stock oysters differ from culture individuals at experimental repopulation conditions in Paz Bay. The total mortality is similar to that for Pinctada radiata in the Red Sea